Digital Tools of Universal Music Education - Parkita, Ewa (Central European Journal of Educational Research, 2021)
The purpose of this article is to present various solutions concerning music education aided by computer technologies. The article applies public music education. The author attempts to provide an answer to questions concerning the role of music teachers working with new media , which requires them to constantly improve and expand their skills. How are they able to utilise new technological achievements while at the same time blending them with well-proven, traditional methods of music teaching/learning, without falling prey to the dangers of modern media ? Any attempts at using innovative solutions are bound to cause numerous challenges for students, teachers, and the entire education system. However, the effects of such actions could contribute to the improvement of the quality of music education in society, which justifies the efforts. The intention of the author is attempt to look into the future on the basis of the existing data sources, analyses and global pedagogical trends and to search for theoretical and practical solutions, which may influence the formulation of the paradigms in modern music teaching.